Effect of High-Flow Oxygen on Exercise Performance in COPD Patients. Randomized Trial - Bitos, Konstantinos; Furian, Michael; Mayer, Laura; Schneider, Simon R.; Buenzli, Simone; Mademilov, Maamed Z.; Sheraliev, Ulan U.; Marazhapov, Nuridin H.; Abdraeva, Ainura K.; Aidaralieva, Shoira D.; Muratbekova, Aybermet M.; Sooronbaev, Talant M.; et al. (Frontiers in Medicine, 2021)
Background: High-flow oxygen therapy (HFOT) provides oxygen-enriched, humidified, and heated air at high flow rates via nasal cannula. It could be an alternative to low-flow oxygen therapy (LFOT) which is commonly used by patients with chronic obstructive pulmonary disease (COPD) during exercise training. Research question: We evaluated the hypothesis that HFOT improves exercise endurance in COPD patients compared to LFOT. Methods: Patients with stable COPD, FEV1 40-80 %predicted, resting pulse oximetry (SpO2) ≥92%, performed two constant-load cycling exercise tests to exhaustion at 75% of maximal work rate on two different days, using LFOT (3 L/min) and HFOT (60 L/min, FiO2 0.45) in randomized order according to a crossover design. Primary outcome was exercise endurance time, further outcomes were SpO2, breath rate and dyspnea. Results: In 79 randomized patients, mean±SD age 58±9 y, FEV1 63±9 %predicted, intention-to-treat analysis revealed an endurance time of 688±463 s with LFOT and 773±471 s with HFOT, mean difference 85 s (95%CI: 7 to 164, P=0.034), relative increase of 13% (95%CI: 1 to 28). At isotime, patients had lower respiratory rate and higher SpO2 with HFOT. At end-exercise, SpO2 was higher by 2% (95%CI: 2 to 2), and Borg CR10 dyspnea scores were lower by -0.8 points (95%CI: -1.2 to -0.3), compared to LFOT. Interpretation: In not-severely hypoxemic patients with COPD, HFOT improved endurance time in association with higher arterial oxygen saturation, reduced respiratory rate and less dyspnea compared to LFOT. Therefore, HFOT is promising for enhancing exercise performance in COPD. Trial registration: ClinicalTrials.gov, NCT03955770.